Postnatal Complementary Care Training Model for Preeclampsy - Rini, Susilo; Soetrisno; Suminah; Andayani, Tri Rejeki (Nusantara Science and Technology Proceedings, 2024)
The highest cause of maternal death in Banyumas Regency, Indonesia in 2022 is preeclampsia during the postpartum period (66.7 percent). However, preeclampsia detection is only carried out if there are symptoms or complaints. Complementary therapies provide a new modality for preventing preeclampsia without having to wait for symptoms to appear. A preliminary study showed that 95.31 percent of midwife who applied complementary therapies had not received training. This research aims to develop a Postnatal Complementary Care Preeclampsia training model for midwives. This research is RnD. Analysis stage with in-depth interviews (6 midwives) and FGD (6 stakeholders). At the Design and Development stage, the training model was prepared and validated by four experts. In the implementation phase, training interventions were carried out on 66 midwives and evaluated using different tests. Results: (1) Analysis: it is necessary to strengthen midwife resources with training to improve the care of preeclampsia postpartum; (2) Design, and create a postnatal complementary care preeclampsia training model; (3) Development, V-Aiken's expert assessment results are in the very high category (mean 0.95) shows the model is valid; (4) Implementation, Independent T-test results show the difference in performance (p-value 0.030 < 0.05), Mann Whitney test results also show the difference in competence (p-value 0.000 < 0.05) which is higher in intervention group, (5) Evaluation, Wilcoxon test results showed (P value 0.006<0.05) the training model was proven to reduce the incidence of preeclampsia in postpartum. The Postnatal Complementary Care Preeclampsia training model is feasible and can be applied as a training guide to improve the competency and performance of midwives to reduce the incidence of postpartum preeclampsia